The Practice of Polygamy in Islam: Rights, Regulations, and Realities - Humaira Mehmood (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
Polygamy, as sanctioned by Islam, continues to be one of the most contentious elements of Islamic family law, frequently misinterpreted both within and beyond Muslim communities. This study analyzes the practice from three fundamental perspectives: rights, rules, and realities. Based on Qur’anic directives, Prophetic traditions, and classical legal interpretations, it delineates the stringent conditions under which a Muslim man may take multiple wives—particularly emphasizing the necessity of fairness, financial capability, and equal treatment. The study examines the rights granted to all parties involved, particularly the frequently neglected protections provided to women. Moreover, it juxtaposes the optimal regulatory structure with the actual experiences in diverse cultural situations, emphasizing both adherence and exploitation. The research aims to elucidate misconceptions and provide a balanced perspective of polygamy's intended role, ethical limitations, and obstacles within contemporary Muslim societies by examining religious ideas in conjunction with current socioeconomic evidence.